Adaptive Bas-relief Generation from 3D Object under Illumination - Zhang, Yu-Wei; Zhang, Caiming; Wang, Wenping; Chen, Yanzhao (Computer graphics forum, 2016)
Bas‐relief is designed to provide 3D perception for the viewers under illumination. For the problem of bas‐relief generation from 3D object, most existing methods ignore the influence of illumination on bas‐relief appearance. In this paper, we propose a novel method that adaptively generate bas‐reliefs with respect to illumination conditions. Given a 3D object and its target appearance, our method finds an adaptive surface that preserves the appearance of the input. We validate our approach through a variety of applications. Experimental results indicate that the proposed approach is effective in producing bas‐reliefs with desired appearance under illumination.